Bibliometric study of business entrepreneurship between 2011 and 2021 in Scopus - Bullón Solís, Omar (2024)
It was developed a bibliometric analysis to identify findings in a set of articles collected under the topic of entrepreneurship in a temporality of ten years. The trends were characterized, predominant authors were identified, the countries with the greatest implication in the development of entrepreneurship, as well as the verification of Lotka's law in scientific production. 4,245 articles were collected from the Scopus database through a systematic search for keywords and filters with the prism method. The bibliometric analysis was performed using the open access software VosViewer and Bibliometrix R. The analysis showed that Shepherd Dean is the leading author in entrepreneurship studies; The trending topic is entrepreneurial ecosystems; the countries that stand out globally are the United States and the United Kingdom; and in the Hispanic world it was Spain and Mexico. The term entrepreneurship is linked to innovation. Finally, it was observed that entrepreneurship promotes the economic development of societies, particularly those that still require an economic boost.